Detection and quantification of silica dust in filtered air samples - Nguyen, Thao (My University, 2021)
Silica is a common mineral in nature. Quartz is the most common form of silica in earth’s crust, while cristobalite and tridymite rarely occur. Quartz can be found in a variety of rocks and soils, and in products such as concrete, brick, granite, sandstone and so on. Any tasks involved in the movement of earth (e.g., mining, quarrying, farming), handling or use of silica-containing products potentially generate silica dust. Successive exposure to respirable crystalline silica (RCS), commonly quartz, may cause silicosis, silico-tuberculosis, lung cancer, and other lung-related diseases. The latency of RCS-related diseases is relatively long, up to 20 years. In some cases, symptoms develop after the period of exposure. These diseases are irreversible and incurable, eventually leading to lung function failure. Unfortunately, the risks of silica dust were overlooked for decades. EU and Finland have set the regulations and occupational limits of RCS to ensure the safety of workers and general publics. Considering the demand of commercial analysis at Top Analytica, the need for silica dust analysis arises mainly from construction industries where workers are exposed to quartz at most. The work presented here gives the quantitative methods for RCS (quartz) in airborne dust at workplaces. The research aims are providing a reliable method that can be used for RCS (quartz) occupational exposure assessment and dust control monitoring at workplaces in order to avoid occupational health problems among silica-exposed workers and meet the regulations. The method using Fourier-transform infrared spectroscopy (FTIR) is developed for commercial analysis. This method is compared with the traditional one using visible spectrophotometry (Vis) in terms of reliability, accuracy, repeatability, and efficiency to reveal its advantages.